1993
DOI: 10.1002/jnr.490350405
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid induces cholinergic differentiation of cultured newborn rat sympathetic neurons

Abstract: Many studies provide evidence that retinoic acid (RA), an endogenous derivative of vitamin A, plays a role in the development of the nervous system. We now report that RA controls the neurotransmitter phenotype of post-mitotic rat sympathetic neurons in cell culture. RA added to the culture medium increased the specific activity of choline acetyltransferase (ChAT) and the level of acetylcholine (ACh). Concomitantly, RA reduced the specific activities of two catecholamine synthetic enzymes, tyrosine hydroxylase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 67 publications
6
31
0
Order By: Relevance
“…New evidence obtained through the application of chromotography and peptide identification via mass spectroscopy on large quantities of rat footpad extract suggests that the sweat gland factor may be cardiotrophin 1 (James Coulombe, personal communication). The observation that LIF triggers the upregulation of ChAT, VAChT, and CHT in cultured sympathetic neurons (Lecomte et al, 2005), while retinoic acid stimulates ChAT and VAChT (Berrard et al, 1993;Berse and Blusztajn, 1995) but suppresses CHT (Lecomte et al, 2005), are consistent with our data suggesting a LIF-related cytokine stimulates expression of all three cholinergic genes in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…New evidence obtained through the application of chromotography and peptide identification via mass spectroscopy on large quantities of rat footpad extract suggests that the sweat gland factor may be cardiotrophin 1 (James Coulombe, personal communication). The observation that LIF triggers the upregulation of ChAT, VAChT, and CHT in cultured sympathetic neurons (Lecomte et al, 2005), while retinoic acid stimulates ChAT and VAChT (Berrard et al, 1993;Berse and Blusztajn, 1995) but suppresses CHT (Lecomte et al, 2005), are consistent with our data suggesting a LIF-related cytokine stimulates expression of all three cholinergic genes in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, previous reports have demonstrated that retinoic acid regulates the expression of ChAT, the enzyme synthesizing ACh, and the vesicular acetylcholine transporter in cell culture (Berrard et al, 1993(Berrard et al, , 1995Kobayashi et al, 1994;Berse and Blusztajn, 1995;Diebler et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This finding, however, still does not prove that the rat glomus cells express cholinergic traits in vivo. Cholinergic gene expression can be induced in sympathetic neurons exposed to conditioned media, CNTF, LIF, or retionic acid in culture (Ernsberger et al, 1989;Lewis et al, 1994;Rao et al, 1992;Berrard et al, 1993Berrard et al, , 1995. Another cholinergic trait, vasoactive intestinal peptide (VIP), can be induced in mature sympathetic ganglion by only exposing the cells to media containing fetal calf serum (Zigmond et al, 1992).…”
Section: Cholinergic Neurotransmitter System Involved In Arterial Chementioning
confidence: 99%